UPAYA MENUMBUHKAN KESADARAN HUKUM DALAM KELUARGA PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Zubairi, Zubairi (STAI Asy-Syukriyyah, 2025)
This research aims to analyze and outline strategic efforts to foster legal awareness within the family environment, prioritizing an Islamic Religious Education (PAI) perspective. As the smallest and primary unit of society, the family plays a crucial role in shaping an individual's character and legal compliance. Low legal awareness can trigger various social problems that disrupt public order.Through a qualitative-descriptive approach with a literature review and normative-theological analysis, this study found that Islamic Religious Education (PAI) offers a solid and effective framework for instilling legal values. Basic concepts in Islam, such as obedience to ulil amri (the ruler), justice (al-'adl), responsibility (mas'uliyyah), and safeguarding the rights of others (huququl 'ibad), are fundamentally aligned with the principles of positive law. Efforts that families can undertake include (1) internalizing sharia values ​​that emphasize the worldly and hereafter consequences of violating the law; (2) cultivating domestic deliberation and justice in decision-making to create a climate of law-abidingness; and (3) exemplary behavior by parents as law-abiding role models. The conclusion of this study is that the integration of Islamic Religious Education (PAI) into family parenting patterns not only produces pious individuals, but also law-abiding and responsible citizens, making PAI a transformative solution in building a law-conscious society.